Discretionary risks disclosure: a management perspective - Roshayani Arshad,; Rina Fadhilah Ismail, (FEP, 2011)
Discretionary risks disclosure practices by managers provide useful information to investors and other users of accounting information in assessing the risk profile of a company. A managers’ ability to disclose relevant risk information that reflects more accurately the companies’ current and future financial performance will facilitate these users in making effective investment decisions. This paper aims to examine empirically the effect of management perception on the disclosure of risk-related information in companies’ annual reports, thus, exploring the current practices of risk reporting by managers of listed companies in Malaysia. The findings should provide useful information to regulators and other policymakers in identifying the factors that influence managers’ perception of risk-related information and, consequently, affect the extent and nature of risk information disclosed in companies’ annual reports. Overall, the findings reveal that enhanced understanding and perception on the overall risk concepts are important drivers that can facilitate managers in disclosing more comprehensive and relevant risk-related information. This, in turn, improves the trust and confidence of investors and other users of financial statements as their evaluations are influenced by the choices of information being disclosed in annual reports by managers.